2020
DOI: 10.2147/cmar.s237467
|View full text |Cite
|
Sign up to set email alerts
|

<p>Validation of the EUTOS Long-Term Survival Score in Chinese Chronic Myeloid Leukemia Patients Treated with Imatinib: A Multicenter Real-World Study</p>

Abstract: These authors contributed equally to this workPurpose: To validate the clinical efficacy of the recently developed EUTOS long-term survival (ELTS) score in a real-world setting. Patients and Methods: A total of 479 chronic myeloid leukemia (CML) patients treated with frontline imatinib between January 2010 and December 2017 were enrolled in this retrospective study. The ELTS score was evaluated on the end-points including complete cytogenetic response (CCyR), progression-free survival (PFS), overall survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
4
5
3
Order By: Relevance
“…ELTS score could predict outcomes of CCyR, PFS, OS, and it was the only scoring system that could predict CML-related death. 17 Our study also provided positive evidence supporting the ELTS score as the most valuable risk stratification tool for CML-CP patients. Even if limited to F I G U R E 3 Cumulative incidence of chronic myeloid leukemia (CML)-related deaths stratified by the scoring systems, according to initial therapy.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…ELTS score could predict outcomes of CCyR, PFS, OS, and it was the only scoring system that could predict CML-related death. 17 Our study also provided positive evidence supporting the ELTS score as the most valuable risk stratification tool for CML-CP patients. Even if limited to F I G U R E 3 Cumulative incidence of chronic myeloid leukemia (CML)-related deaths stratified by the scoring systems, according to initial therapy.…”
Section: Discussionsupporting
confidence: 68%
“…Another recent study from China, which investigated patients treated with imatinib as first‐line therapy, presented the prognostic value of the ELTS score compared with the other three risk scores. ELTS score could predict outcomes of CCyR, PFS, OS, and it was the only scoring system that could predict CML‐related death 17 . Our study also provided positive evidence supporting the ELTS score as the most valuable risk stratification tool for CML‐CP patients.…”
Section: Discussionsupporting
confidence: 62%
“…13 Yang et al reported 5-year OS probabilities of 98% (95% confidence interval [CI]: 96-100%), 89% (95% CI: 83-95%) and 79% (95% CI: 78-91%) in the low-, intermediate-, and high-risk ELTS groups (p = 0.001 and 0.009 for high versus low and high versus intermediate risk groups). 14 Cortes et al reported two (3.2%) instances of QTc prolongation, whereas in our study group it is observed in four (9.7%) patients. 15 Saglio et al reported toxicity-related discontinuation rates of 5%.…”
Section: Discussioncontrasting
confidence: 76%
“…While Yang et al observed the most distinct risk group discrimination of OS probabilities with the ELTS score in 462 imatinib-treated Chinese patients with a median follow-up of 69 months [25], Millot et al found that its three risk groups differed significantly from each other with respect to progression-free survival in 350 children with imatinib as first-line treatment-despite only 23 events (progression or death) [26]. In both studies, the authors concluded that the ELTS score outperformed all other scores [25,26]. However, instead of the conventional Sokal score, Millot et al considered the Sokal score for younger patients (≤45 years) [26,27].…”
Section: Discussionmentioning
confidence: 98%
“…The ELTS score has been validated several times for its ability to significantly discriminate risk groups regarding long-term survival outcome but mainly in patients first-line treated with imatinib [6,8,15,[24][25][26]28]. Despite significantly faster achievement of molecular reponses with second generation TKIs [10,13,[30][31][32][33], first-line treatment with imatinib and its generics is still widespread.…”
Section: Discussionmentioning
confidence: 99%